IMPROVING THE EFFICIENCY OF WORK OF MANAGEMENT COMPANIES IN HOUSING AND COMMUNAL SERVICES - Evgeniy Ignatievich Belyaev; Iola Ynovna Kuklite (Современная наука и инновации, 2022)
A comparative analysis of the results of the housing management of different forms of governance. Discusses the possible use of the new organizational structure matrix type management company to improve management efficiency in the housing sector.